Síntese e caracterização estrutural de pigmentos cerâmicos a base de cromita por método químico - Rangel, José Hilton Gomes; Pereira, Edilson Batista S.; Gonçalves Júnior, Paulo Roberto Garcês; Oliveira, Marcelo Moizinho; Vasconcelos, Jomar Sales; Silva, Elson Longo da [UNESP] (My University, 2012)
The ceramic pigments are colored inorganic substances that during the process of dispersion in the ceramic glazes and subsequent calcination, are stable against physical and chemical attack. Therefore, they are crystalline compounds applied in the ceramic industry for coloring vitreous base. In this study, the Pechini method was used for obtaining the pigment CuCr2O4 with heat treatment at the temperatures of 800, 900 and 1000 ° C. The powder pigments were characterized on their structural, morphological and colorimetric aspects. The thermal analysis conducted on an amorphous precursor in a TG / DTA indicates the weight loss in the entire temperature range investigated, with characteristic exothermic peak of the elimination of the organic composition of the precursor around 300°C. The development of the crystalline phases were investigated by XRD, using a diffractometer with Cu Ka radiation and graphite monochromator, where it was observed the presence of crystalline phases corresponding to Cr2O3 and CuCr2O4.The measurements of the specific surface area of the powders pigments were carried out in an equipment Micromeritcs, model ASAP 2000, using N2 as gas of adsorption/desorption. The colorimetric measurements of the pigments were made in a colorimeter Gretac Macbeth Color-eye spectrophotometer 2180 / 2180UV in CIELAB standards. Based on the obtained results, it can be verified the thermal stability of the powder pigments of green coloration, which enables it as an alternative to the materials currently used in the manufacture of ceramic tiles.

Os pigmentos cerâmicos são substâncias inorgânicas coloridas que durante o processo de dispersas nos esmaltes cerâmicos e posterior calcinação, se mantêm estáveis frente ao ataque físico e químico. Por conseguinte, são compostos cristalinos aplicados na indústria cerâmica para colorir bases vítreas. Neste trabalho foi utilizado o método Pechini na obtenção do pigmento CuCr2O4 com tratamento térmico nas temperaturas de 800, 900 e 1000 °C. Os pós pigmentantes foram caracterizados nos aspectos estruturais, morfológicos e colorimétricos. A análise térmica realizada no precursor amorfo em um TG/DTA revela a perda de massa em todo o intervalo de temperatura investigado, com pico exotérmico característico da eliminação da composição orgânica do precursor em torno de 300°C. A evolu- ção das fases cristalinas foi investigada por DRX, utilizando um difra de grafite onde se observou a presença de fases cristalinas correspondentes ao Cr2O3 e CuCr2O4. As medidas de área superficial específica dos pós pigmentantes foram realizadas em um equipamento Micromeritcs modelo ASAP 2000, utilizando N2 como gás de adsorção/desorção. As medidas colorimétricas dos pigmentos foram realizadas em um colorímetro Gretac Macbeth Color-eye spectrophotometer 2180/ 2180UV, nos padrões CIELAB. Com base nos resultados obtidos verifica-se a estabilidade térmica dos pós pigmentantes de coloração verde, o que o habilita como alternativa aos materiais atualmente empregados na indústria de pisos cerâmicos.
Synthesis and structural characterization of chromites ceramic pigments by chemical method
Keywords: espinélio; Cromita de cobre; Pigmento inorgânico; Pechini; Spinels; Chromite Copper; Inorganic Pigment; Pechini